Nutzung von Radwegen in Gegenrichtung - Sicherheitsverbesserungen. - (:unkn) unknown (My University, 2015)
Cyclists who ride on cycle paths in the wrong direction (on the left) are exposed to high risks. The Federal Highway Research Institute (BASt) examined whether the hazards are equally high for cyclists riding on the left on cycle paths that are usable on both sides. As a result, action strategies could be developed to enhance safety. Inner-city cycle paths in the opposite direction should only be approved in exceptional cases. A clarification of the provisions of the administrative regulations for the road traffic regulations (StVO) is considered appropriate for the approval of cycle paths on the left. At the same time, special consideration should be given to critical junctions and access roads. Compliance with sufficient visual links must be ensured. With additional safety measures, such as pictograms with direction arrows, red colouring of the bicycle traffic and structural measures in particular, a noticeable increase in safety can be achieved. Of particular importance is the awareness of cyclists about the dangers of riding on the left. There should be increased police monitoring of roads with relatively high accident frequencies.
Keywords: Individualverkehr; Fahrradverkehr; Infrastruktur; Verkehrssicherheit; Fahrradweg; Radweg; Radverkehrsanlage; Fahrradinfrastruktur; Radverkehrssicherheit; Fahrtrichtung